The Role of Optimism towards Grit in Mothers Who Have Children With Intellectual Disabilities: Peran Optimisme terhadap Grit pada Ibu yang Memiliki Anak dengan Disabilitas Intelektual - Nuraeni, N; Suwartono, S; Wahidah, Fatin Rohmah Nur (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The mother is the first person to feel guilt for failing to give birth to a normal child. Mothers who have children with intellectual disabilities must be persistent in caring for their children so that their hopes and aspirations can be carried out well. The effort is to be optimistic in accompanying children to achieve their hopes and dreams. The aim of the research is to examine the role of optimism on grit in mothers with children with intellectual disabilities. The specific target of this research is that optimism influences grit in mothers of children with intellectual disabilities. This research uses quantitative research methods. The research participants were 74 mothers with children with intellectual disabilities who attended SLB C (intellectual disabilities). The research location was SLB C Yakut Purwokerto. Research result; optimism has a significant effect on grit in mothers of children with intellectual disabilities.